Republic of Equatorial Guinea : Staff Report 2006 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
Equatorial Guinea's macroeconomic performance in the recent period has been broadly satisfactory. Despite the macroeconomic environment, however, progress in alleviating poverty and meeting the MDGs has been slow. Executive Directors welcome the government's intention to prepare a National Poverty Reduction Strategy. In the meantime, the budget process needs to be modified. The pegged exchange rate regime has served Equatorial Guinea well, providing an anchor to hold down inflation and a positive influence on investors' confidence. The data provided by Equatorial Guinea are broadly adequate for surveillance.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet